A study on the carbon emission reduction pathways of China’s digital economy from multiple perspectives - Shi, Xiaoyan; Zhu, Zhenhua; Wu, Jiaxin; Li, Zhijiang (Frontiers in Environmental Science, 2025)
As the share of the digital economy’s output continues to rise each year, the emergence of new industries such as e-commerce, mobile payments, and cloud computing has opened new avenues for carbon emission reduction (CER). Based on panel data from 30 provinces in China, this article systematically analyzes the CER pathways of China’s digital economy (DE) from the perspectives of direct effects, indirect effects, threshold effects, and heterogeneity analysis. The main conclusions are as follows: (1) China’s DE has a significant CER effect. (2) The DE can indirectly reduce regional carbon emissions (CE) by industrial structures and technological innovation, with the mediating effect of technological innovation being more significant than that of industrial structure. (3) Urbanization has threshold effects on the CER effect of China’s DE. Under the influence of urbanization, there is an inverted U-shaped relationship between DE and CE. (4) Heterogeneity analysis finds that, compared to other types of provinces, the CER effect of DE is stronger in non-resource-based and economically developed provinces. (5) We propose five tailored recommendations for CER: fostering the synergistic development of the DE and industrial structure, strengthening the role of technological innovation, advancing urbanization and carbon reduction in a differentiated manner, formulating distinct policies for resource-based and non-resource-based provinces, and enhancing the construction of digital infrastructure in less-developed regions. This article not only establishes a more comprehensive connection between the DE and CER, but also reveals the differences in the role of technological innovation, industrial structure optimization, urbanization and other factors in the carbon reduction effect of the DE through the comparison of different paths and mechanisms.